Deployment and Post-Deployment Experiences in OEF/OIF Veterans: Relationship to Gray Matter Volume - Aupperle, Robin L. (Public Library of Science, 2013)
BACKGROUND: Combat-related PTSD has been associated with reduced gray matter volume in regions of the prefrontal and temporal cortex, hippocampus, insula, and amygdala. However, the relationship between gray matter volume and specific deployment and post-deployment experiences has not been investigated. The aim of this study was to delineate how such experiences may contribute to structural brain changes for combat veterans. METHODS: Operation Iraqi Freedom/Operation Enduring Freedom veterans (N = 32) completed magnetic resonance imaging, the Deployment Risk and Resilience Inventory, Alcohol Use Disorders Identification Test, and Clinical Administered PTSD Scale. Voxel-wise Huber robust multiple regressions were used to quantify the relationship between gray matter volume and deployment experiences (combat experiences, military social support) and post-deployment symptoms (PTSD, alcohol use). RESULTS: There was an interaction between severity of combat experiences and military social support for orbitofrontal gyrus gray matter volume. Specifically, individuals with more orbitofrontal gyrus gray matter volume reported less combat experiences and higher unit support. Individuals with more severe PTSD symptoms showed reduced gray matter volume within a large temporal region (inferior temporal and parahippocampal gyrus). CONCLUSIONS: The identified association between unit support and orbitofrontal gyrus volume supports two potential resilience mechanisms to be delineated with future longitudinal studies. First, individuals with larger orbitofrontal gyrus may engage in greater quality of social interactions and thus experience combat as less stressful. Second, individuals who experience greater unit support may preserve a larger orbitofrontal gyrus, serving to “protect” them from aversive consequences of combat.